Spirited away [videorecording (DVD)] - Miyazaki, Hayao, 1941-; Holly, Lauren (Shout Factory, 2017)
A young girl, Chihiro, finds herself trapped in a strange new world of spirits. When her parents undergo a mysterious transformation, she must call on the courage she never knew she had to free herself and return her family to the outside world. An unforgettable story, brimming with creativity, this will take viewers on a journey beyond imagination.